The Dervishes of the North : Rumi, Whirling, and the Making of Sufism in Canada. - Xavier, Merin Shobhana. (University of Toronto Press, 2023)
The Dervishes of the North traces the legacy of the thirteenth-century Muslim mystic and poet, Jalal al-Din Rumi, and examines contemporary Sufism in Canada.